Incidental Durotomy Following Surgery for Degenerative Lumbar Disease and the Impact of Minimally Invasive Surgical Technique on the Rate and Need for Surgical Revision: A Case Series. Issue 5 (30th August 2021) - Mueller, Kyle B; Garrett, Coleman T; Kane, Stephen; Sandhu, Faheem A; Voyadzis, Jean-Marc
Abstract: BACKGROUND: Incidental durotomy (ID) is a common complication during lumbar spine surgery. A paucity of literature has studied the impact of minimally invasive surgery (MIS) on durotomy rates and strategies for repair as compared to open surgery. OBJECTIVE: To examine the impact that MIS techniques have on the durotomy rate, repair techniques, and need for surgical revision following surgery for degenerative lumbar disease as compared to open technique. METHODS: A single-center retrospective review of consecutive cases between 2013 and 2016 was performed. All patients underwent lumbar decompression with or without instrumented fusion for degenerative pathology using either open posterior or MIS techniques. ID rate, closure technique, and need for surgical revision related to the durotomy were recorded. RESULTS: A total of 1, 196 patients were included with an overall ID rate of 6.8%. There was no difference between open or minimally invasive surgical techniques ( P  = .14). There was a higher durotomy rate with open technique in patients that underwent decompression with fusion ( P  = .03) as well as in revision cases ( P  = .02). Primary repair was feasible more frequently in the open group ( P  = .001), whereas use of dural substitute ( P < .001) was more common in the MIS group. Fibrin sealant was used routinely in both groups ( P  = .34). There were no failed repairs, regardless of technique used. CONCLUSION: MIS techniques may reduce durotomies in cases involving instrumentation or revisions. Use of dural substitute onlay and fibrin sealant was effective at preventing reoperation. Both MIS and open techniques result in a low rate of future surgical revision when a durotomy occurs.